Bulachite, [Al6(AsO4)3(OH)9(H2O)4]⋅2H2O from Cap Garonne, France: Crystal structure and formation from a higher hydrate. (30th August 2020) - Grey, Ian E.; Yoruk, Emre; Kodjikian, Stéphanie; Klein, Holger; Bougerol, Catherine; Brand, Helen E.A.; Bordet, Pierre; Mumme, William G.; Favreau, Georges; Mills, Stuart J.
Abstract: Bulachite specimens from Cap Garonne, France, comprise two intimately mixed hydrated aluminium arsenate minerals with the same Al:As ratio of 2:1 and with different water contents. The crystal structures of both minerals have been solved using data from low-dose electron diffraction tomography combined with synchrotron powder X-ray diffraction. One of the minerals has the same powder X-ray diffraction pattern (PXRD) as for published bulachite. It has orthorhombic symmetry, space group Pnma with unit-cell parameters a = 15.3994(3), b = 17.6598(3), c = 7.8083(1) Å and Z = 4, with the formula [Al6 (AsO4 )3 (OH)9 (H2 O)4 ]⋅2H2 O. The second mineral is a higher hydrate with composition [Al6 (AsO4 )3 (OH)9 (H2 O)4 ]⋅8H2 O. It has the same Pnma space group and unit-cell parameters a = 19.855(4), b = 17.6933(11) and c = 7.7799(5) Å i.e. almost the same b and c parameters but a much larger a parameter. The structures are based on polyhedral layers, parallel to (100), of composition [Al6 (AsO4 )3 (OH)9 (H2 O)4 ] and with H-bonded H2 O between the layers. The layers contain [001] spiral chains of edge-shared octahedra, decorated with corner connected AsO4 tetrahedra that are the same as in the mineral liskeardite. The spiral chains are joined together by octahedral edge-sharing to form layers parallel to (100). Synchrotron PXRD patterns collected at different temperatures during heating of the specimen show that the higher-hydrate mineral starts transforming to bulachite when heated to 50°C, and the transformation is complete between 75 and 100°C.